Bahasa Inggris - Ahmad Minanur Rohim; Putut Marwoto; Sigit Priatmoko; Almira Syifa (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to compare packaged and bulk cooking oils. The FTIR test, viscosity, density, acid number, and organoleptic are all used as research methods. With FTIR results on the C-H spectral group of alkanes seen at 1463.78 cm-1 and 1743.63 cm-1, and the tertiary C=O ester group of triglyceride seen at 1743.66 cm-1 and 1743.63 cm-1. It was determined that bulk cooking oil includes more hydrogen and double bonds than packaged cooking oil. Bulk cooking oil viscosity testing with packaging showed that it was between 38 and 37 MPa, had densities of 0.92 and 0.90 gr/ml, and acid numbers of 0.18 and 0.11 mg of potassium hydroxide. Packaged cooking oil has a more appealing aroma than bulk cooking oil, and both have a sticky flavor. Bulk cooking oil is dark, but packaged oil is yellow. According to the study of the test results, bulk cooking oil is of lower quality and has a greater impact than packaged oil.